Cognitive and Neurolinguistic Aspects of Advertising Discourse Perception - Egamberdieva, Farida; Egamberdieva, Shakhzoda (Indonesia Academia Research Society, 2024)
This study examines how cognitive and neurolinguistic mechanisms influence consumer behavior and decision-making in advertising. It explores the roles of attentional salience, memory encoding, and emotional responses in shaping how advertisements affect audiences. Attention is critical, driven by visual stimuli (e.g., colors, motion) and top-down processes based on personal goals and cultural relevance. Memory encoding is supported through repetition, rhyme, and the integration of verbal and visual cues, while emotional triggers engage the amygdala, enhancing retention. Neurolinguistic techniques, such as semantic priming, create subconscious associations between words, images, and brand values, accelerating comprehension and promoting positive perceptions. For example, luxury brands use semantic cues to suggest exclusivity, while metaphors activate sensory and cognitive areas, strengthening engagement. Additionally, advertising content is processed through hemispheric lateralization, with the left hemisphere focusing on linguistic aspects and the right hemisphere processing visuals and emotions. This study underscores the significance of incorporating these cognitive and neurolinguistic principles into advertising. Examples include Coca-Cola’s use of visual icons for universal attention, Nike’s use of memorable slogans for retention, and Dove’s emotional appeals for loyalty. Also, culturally tailored approaches, such as aligning metaphors with societal norms, enhance relevance across diverse audiences. The research suggests using neuroimaging tools, like fMRI and EEG, to identify neural correlates of engagement. It emphasizes the potential of machine learning and neuromarketing in customizing advertisements based on individual neural responses. Integrating these principles can help create emotionally and cognitively impactful campaigns.